CREATIVITY AND LEADERSHIP - Vukadinović, Maja (International Journal of Economic Practice and Policy, 2024)
The aim of this paper is to analyse the relationship between leadership and creativity, to compare the characteristics of a successful leader and the characteristics of a creative person and to find out how they may be linked. It is hypothesized that creativity represents one of the most important traits a successful leader should have. It is presumed that creativity unites originality, openness, sensibility, flexibility, fluency of ideas, fantasy, tolerance of uncertainty, creative generalization, creative differentiation and that it can be recognized through them. This study is qualitative and it is based on analyses and comparison of the results of different studies in the domain of leadership and creativity. The result of our analyses has shown that even though creativity is not listed among the key characteristics of a leader (e.g. intelligence, self-confidence, decisiveness and integrity), it should be recognized as such. The main contribution of this study lays in acknowledging creativity as a component sine qua non of successful leadership. The main implication of our results is related to the thesis that encouragement, development and implementation of creativity in every part of leadership process should result in greater success in every business domain where leadership is necessary. The main recommendation which follows from our results is to encourage and enhance the use of creativity in every domain of business, especially leadership. Moreover, empirical exploration regarding the relationship between attributes of creativity and characteristics of a successful leader is recommended.